Liquid moisture transport in combined ceramic brick and natural hydraulic lime mortar samples: Does the hygric interface resistance dominate the moisture transport?. (November 2019) - Calle, Klaas; De Kock, Tim; Cnudde, Veerle; Van den Bossche, Nathan
To reduce the energy use of the European building stock, a large potential can be found in the renovation of cultural heritage buildings. However, insulating these valuable masonry facades often increases the risk of moisture-related damage phenomena such as mold growth and frost damage. Therefore, detailed heat, air and moisture simulations are required to quantify and assess these risks. One of the unknown parameters in the simulations for historic masonries is the hygric interface resistance between the bricks and the lime mortars. Consequently, microfocus X-ray scans are performed during a capillary water absorption test on brick–lime mortar–brick samples to increase the insight into the moisture transport over the interface, dependent on the capillary pressure at the interface and the curing conditions of the mortar. The hygric interface resistance is found to be highly dependent on both capillary pressure and the curing conditions of the mortar. For the exact quantification of the interface resistance, highly detailed moisture transport and moisture storage properties of the brick and mortar are a prerequisite.